Does language matter? an exploration of social capital in Malaysian online ethnic communities - Wan Jaafar, Wan Munira (Infobase Creation, 2015)
The term “social capital” originated out of a discourse in developing community networks. In brief, it shows a cooperative model where people work with an underlying basis that the more one knows, the more ties one holds in connecting with community members. The changing nature of social relationships resulting from advances in today’s new communication technology has brought about the idea of applying this concept within the context of online communities. This research empirically addresses the issues of social capital and ethnic integration in a study of six selected online communities in Malaysia. The main methods of data collection were online survey across 162 online community’s members and interview of 8 online community’s administrators. Results showed that, in many ways, online networking does facilitate interactions between members but most of the basic elements, as suggested by the concept of social capital, such as trust and norms of reciprocity, have been contested by various socio-cultural issues. The different needs served by online community members, along with the fact that society is still much influenced by various cultural capitals such as languages have arguably limited the way social capital can be developed across ethnic lines. Therefore, utilizing this concept in terms of online networking and socialization was actually a challenging and at times ambiguous process.